Can We Empower Patients for Joint Surgery? Assessing the Impact of a Telemedicine Coaching Intervention - Christopher Q. Lin, MS; Hikmat R. Chmait, MS; Jordan P. Conroy, MD, MS; Nathaniel J. Nelms, MD; Michael Blankstein, MD, MSc, FRCSC (Arthroplasty Today)
Background: Optimizing patients before surgery results in fewer complications and higher patient quality of life following surgery. We implemented a telemedicine Joint Health Coaching program in 2020 to address risk factors in patients who were otherwise candidates for hip or knee arthroplasty. The aim of the study was to evaluate the results of our 3-year program. Methods: Patients presenting at our total joint arthroplasty clinic between January 2020 and March 2023 who were surgical candidates were offered enrollment in the telemedicine Joint Health Coaching program. Patients who failed to attend at least 1 coaching session were excluded. Certified health coaches then provided counseling on nutrition, exercise, and smoking cessation. Patients were then assessed by changes in body mass index, hemoglobin (HbA1c), disability scores, and quality of life measures and compared to their initial values. Results: Two hundred ninety-two of 323 patients had a goal involving weight management. One hundred thirty-four experienced a decrease in body mass index, with 17% achieving clinically significant weight loss (> 5%). Fifty-two percent of patients targeting smoking cessation succeeded, and those addressing diabetes saw an average decrease in HbA1c by 0.24. Patient-reported outcome measures after 3 months of preoperative coaching revealed an improvement in quality of life score for knee patients (P < .001). Regression analysis showed physical therapy, hip involvement, and lower HbA1c were associated with greater weight loss. Opioid use, smoking, and absence of glucocorticoid injections were associated with less weight loss. Conclusions: A telemedicine-based approach to optimization offered modest yet significant health improvements in a subset of patients. Telemedicine may offer a cost-effective approach to presurgical optimization.